Novel Insight Into Long-Term Risk of Major Adverse Cardiovascular and Cerebrovascular Events Following Lower Extremity Arteriosclerosis Obliterans - Sun, Ji; Deng, Qiang; Wang, Jun; Duan, Shoupeng; Chen, Huaqiang; Zhou, Huixin; Zhou, Zhen; Yu, Fu; Guo, Fuding; Liu, Chengzhe; Xu, Saiting; Song, Lingpeng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Patients with lower extremity arteriosclerosis obliterans (LEASO) are more likely to appear to be associated with adverse cardiovascular outcomes. Currently, few studies have reported the sex-specific characteristics and risk of major cardiovascular and cerebrovascular adverse events (MACCEs) in LEASO. Our study was conducted to determine the characteristics and contributions of LEASO to MACCEs in males and females. Methods: We conducted a single-center retrospective study of consecutively enrolled patients with first-diagnosed LEASO at Renmin Hospital of Wuhan University from December 2017 to December 2020. The ratio of patients between the LEASO and control groups was 1 to 1 and based on age, sex, comorbid diabetes mellitus and hypertension, current smoking and medications. The occurrence of MACCEs was used as the primary endpoint of this observational study. Results: A LEASO group (n=430) and control group (n=430) were enrolled in this study. A total of 183 patients experienced MACCEs during an average of 38.83±14.28 months of follow-up. Multivariate Cox regression analysis indicated that LEASO was an independent predictor of the occurrence of MACCEs in all patients (HR: 2.448, 95% CI: 1.730-3.464, P<0.001). Subgroup analysis by sex subgroup was conducted for sex, and LEASO was also an independent predictor of the occurrence of MACCEs in both male cases (HR: 2.919, 95% CI: 1.776-4.797, P<0.001) and female cases (HR: 1.788, 95% CI: 1.110-2.880, P=0.017). Moreover, Kaplan–Meier analysis indicated no significant difference in event-free survival between patients of different sexes with LEASO (χ2=0.742, P=0.389). Conclusion: LEASO tended to a useful risk stratified indicator for MACCEs in both male and female patients in our study. Notably, attention should be given to patients with LEASO who should undergo comprehensive cardiovascular evaluation and intervention, even if there is a lack of traditional cardiovascular risk factors.